Statement of retraction - Baublys, Adolfas; Prentkovskis, Olegas (Transport, 2012)
„Statement of retraction" Transport, 27(3), p. 344 This article refers to: Modelling of freight flows that consist of multiple products transported by different modes of transport in a multimodal network First Published Online: 19 Sep 2012